A highly active self-supporting bifunctional water electrolysis catalyst and its preparation and application
By forming a CoNiCu-LDH catalyst with a nanoflower layer structure on copper foam, the problems of high overpotential and high cost of precious metal catalysts in water electrolysis technology are solved, and electrocatalytic performance with low energy consumption and high stability is achieved.
Patent Information
- Application Number
- CN202211246655.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-10-12
AI Technical Summary
The existing water electrolysis technology has problems with high overpotential and energy consumption when producing high purity hydrogen, and the precious metal catalysts used are costly and scarce, limiting its large-scale application.
A self-supporting bifunctional water electrolysis catalyst with a nanoflower layer structure of CoNiCu-LDH loaded on copper foam is used to form a stable three-dimensional structure on the electrode through steps such as redox and solvothermal methods.
It achieves good electrocatalytic oxygen evolution and hydrogen evolution performance in alkaline electrolytes, with low overpotential and high stability, reducing energy consumption and improving the long-term stability of the catalyst.
Smart Images

Figure CN115573000B_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the field of electrocatalysis, and in particular relates to a self-supporting bifunctional water electrolysis catalyst and a preparation method thereof. Background technology:
[0002] Hydrogen is one of the most ideal alternative energy carriers to traditional fossil fuels, with the following outstanding advantages: (1) Energy density (142 MJ / Kg) is much higher than gasoline (44 MJ / Kg); (2) Wide range of uses: Not only can it be used as a fuel, but it is also an important industrial raw material in many chemical processes, such as the Fischer-Tropsch reaction and ammonia synthesis reaction; (3) It is easy to transport; (4) It can release energy through direct combustion or reaction in hydrogen fuel cells, and the only byproduct is water. Therefore, hydrogen is considered to be one of the most promising clean energy sources in the 21st century. However, to date, the main methods for industrial hydrogen production are still steam methane reforming and coal gasification. The hydrogen produced by these processes is of low purity, consumes a large amount of fossil fuels, and emits a large amount of pollutants and CO2. Therefore, there is an urgent need to seek clean and sustainable hydrogen production strategies.
[0003] Water electrolysis is an efficient and clean industrial hydrogen production technology that can produce high-purity hydrogen. Electrochemical water splitting consists of two half reactions: the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Although water electrolysis provides an effective way to produce high-purity hydrogen, the practical application of electrochemical water splitting to produce hydrogen is also limited because it is a strong uphill reaction with a large overpotential. The use of OER and HER electrocatalysts is an effective way to reduce the overpotential of water splitting, which can reduce energy consumption and increase energy utilization efficiency. An ideal HER and OER catalyst must meet two basic requirements: first, the electrocatalyst must be highly active and can produce a larger current density at a smaller overpotential; second, it must exhibit long-term stability. Currently, platinum group metals with Ir and Ru oxides are the benchmark electrocatalysts for HER and OER, respectively, but the scarcity and high cost of these precious metals seriously hinder their large-scale practical application. Summary of the invention:
[0004] In view of the above problems, the present invention provides a self-supporting bifunctional water electrolysis catalyst and a preparation method thereof.
[0005] To achieve the above purpose, the present invention adopts the following technical solution:
[0006] A highly active self-supporting bifunctional water electrolysis catalyst, wherein the catalyst is a nano-flower layer structure of CoNiCu-LDH loaded on a copper foam (CF) to form a three-dimensional self-supporting stable structure; wherein the catalyst loading is about 5-20 mg cm -2, preferably 5-10 mg cm -2 .
[0007] A method for preparing a highly active self-supporting bifunctional water electrolysis catalyst, wherein Cu(OH)2 nanowires are directly grown in situ on the surface of copper foam by a redox method, and then placed in a Co-containing 2+ and Ni 2+ A core-shell structure precursor is formed in a mixed solution of a metal salt and terephthalic acid, and the core-shell structure precursor is then immersed in a solvent containing a nickel salt and a cobalt salt to form a cobalt-nickel layered double hydroxide (CoNiCu-LDH) on the foamed copper through a solvothermal method.
[0008] Specifically:
[0009] 1) At room temperature, the copper foam is placed in an aqueous solution of NaOH and (NH4)2S2O8 for chemical oxidation to obtain a precursor 1;
[0010] 2) adding nickel salt, cobalt salt and terephthalic acid to the mixed solution, stirring at room temperature to obtain a mixed solution; placing precursor 1 in the mixed solution to synthesize precursor 2 by hydrothermal method, and washing and drying after the reaction;
[0011] 3) The precursor 2 obtained in step 2) is immersed in an ethanol solution containing nickel salt and cobalt salt for hydrothermal synthesis, and washed and dried after the reaction to obtain a bifunctional water electrolysis catalyst.
[0012] In the step 1), the final concentration of NaOH in the aqueous solution of NaOH and (NH4)2S2O8 is 1 mol / L-5 mol / L, and the concentration ratio of NaOH to (NH4)2S2O8 is 5:1-20:1.
[0013] The nickel salt, cobalt salt and terephthalic acid are added to a mixed solution, and the total final concentration of the nickel salt, cobalt salt and terephthalic acid in the mixed solution is 1mmol / L-3mmol / L, wherein the molar ratio of the nickel salt, cobalt salt and terephthalic acid is 1:1:1.5-1:1:3.
[0014] The mixed solution is prepared by sequentially mixing methylformamide, ethanol and ultrapure water in a volume ratio of 12:1:1.
[0015] The nickel salt is one or more of nickel nitrate hexahydrate, nickel sulfate hexahydrate, nickel chloride hexahydrate, and nickel bromide; the cobalt salt is one or more of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, and cobalt acetate tetrahydrate.
[0016] In the step 2), the precursor 1 is placed in a mixed solution at 70°C-150°C for a solvent thermal synthesis reaction for 10-14 hours, washed with ethanol after the reaction, and dried at 60°C-100°C to obtain the precursor 2.
[0017] In the step 3), the precursor 2 obtained in the step 2) is immersed in an ethanol solution containing nickel salt and cobalt salt at 110°C-140°C for hydrothermal synthesis for 2-4h, and after the reaction, it is washed with ethanol and dried at 60°C-100°C to obtain a bifunctional water electrolysis catalyst; wherein the total final concentration of nickel salt and cobalt salt in ethanol is 1mmol-3mmol, and the molar ratio of nickel salt to cobalt salt is 1:1.
[0018] An application of a water electrolysis catalyst, and application of the catalyst in a water electrolysis reaction.
[0019] The advantages of the present invention are:
[0020] 1. The catalyst of the present invention is a bifunctional CoNiCu-LDH@CuO / CF self-supporting electrode, which can effectively split water. It uses CoNiCu-MOF as a precursor, changes the growth process of CoNiCu-LDH through a rapid phase change process, and obtains a nanoflower structure with a surface rich in active sites, which has excellent electrocatalyst performance.
[0021] 2. The preparation process of the present invention is simple to operate and controllable, the raw material cost is low, the catalyst performance is good, and it has the potential for industrial application.
[0022] 3. The catalyst of the present invention exhibits good electrocatalytic oxygen and hydrogen evolution performance in alkaline electrolytes, and has the characteristics of low overpotential and strong catalytic stability. Description of the drawings:
[0023] Figure 1 The electrochemical performance test results of the products obtained in Example 1 and Comparative Examples 1-2 of the present invention are shown in FIG. Figure 1 a is the OER test LSV curve, Figure 1 b is the EIS diagram of OER test, Figure 1 c is the LSV curve of HER test, Figure 1 d is the EIS graph of HER test.
[0024] Figure 2 This is a graph showing the electrocatalytic performance of the product obtained in Example 1 of the present invention for the complete hydrolysis of water, wherein Figure 2 a is the LSV curve of complete water decomposition, Figure 2 b is the stability diagram of complete water decomposition.
[0025] Figure 3 SEM image of the catalyst prepared in Example 1
[0026] Figure 4 TEM image of the catalyst prepared in Example 1
[0027] Figure 5 XRD pattern of the catalyst prepared in Example 1
[0028] Figure 6 SEM image of the catalyst prepared in Comparative Example 2 Specific implementation method:
[0029] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments described below can be arbitrarily combined to form a new embodiment.
[0030] Embodiment 1:
[0031] A copper-based self-supporting water electrolysis catalyst, the preparation process of which comprises the following steps:
[0032] (1) First, a piece of copper foam (CF) is ultrasonically cleaned in acetone, ethanol and deionized water in turn to remove surface impurities. The cleaned CF is immersed in an aqueous solution containing NaOH (2.0 M) and (NH4)2S2O8 (0.1 M) for about 10 to 30 min. The light blue Cu(OH)2 / CF is taken out from the solution, washed, dried and set aside.
[0033] (2) First, weigh 0.124 g of terephthalic acid and place it in a beaker. Then, add ethanol, ultrapure water, and organic solvent dimethylformamide (wherein the volume ratio of dimethylformamide, alcohol, and ultrapure water is 12:1:1) in sequence. After stirring evenly at room temperature, add 0.267 g of Ni(NO3)2·6H2O and 0.267 g of Co(NO3)2·6H2O. After continuous stirring at room temperature for 6 hours, transfer the mixture to the polytetrafluoroethylene liner of a hydrothermal autoclave, place the Cu(OH)2 / CF obtained in step (1) in the autoclave, seal the autoclave, and place the autoclave in an oven at 140°C for 12 hours. Subsequently, take the autoclave out, wash it with dimethylformamide, ethanol, and water in sequence, and dry it to obtain a dark brown CoNiCu-MOF@Cu2O / CF.
[0034] (3) 0.3 g Ni(NO3)2·6H2O and 0.3 g Co(NO3)2·6H2O were dissolved in 30 mL ethanol solution and stirred evenly. The above solution was then transferred to a 50 mL stainless steel reactor, and the prepared CoNiCu-MOF@Cu2O / CF was placed in it. After sealing, the reactor was placed in an oven and kept at 120°C for 3 hours. Then, it was taken out for washing and drying to obtain a bifunctional water electrolysis catalyst CoNiCu-LDH@CuO / CF composite material. The mass difference before and after the copper foam was loaded was measured by a microbalance, and the loading amount was 5 mg cm-2 (See Figure 3-5 )
[0035] Embodiment 2:
[0036] A copper-based self-supporting water electrolysis catalyst, the preparation process of which comprises the following steps:
[0037] (1) First, a piece of copper foam (CF) is ultrasonically cleaned in acetone, ethanol and deionized water in turn to remove surface impurities. The cleaned CF is immersed in an aqueous solution containing NaOH (2.0 M) and (NH4)2S2O8 (0.1 M) for about 10 to 30 min. The light blue Cu(OH)2 / CF is taken out from the solution, washed, dried and set aside.
[0038] (2) First, 0.124 g of terephthalic acid was weighed and placed in a beaker, and then ethanol, ultrapure water, and organic solvent dimethylformamide were added in sequence (wherein the volume ratio of dimethylformamide, alcohol, and ultrapure water was 12:1:1). After stirring at room temperature, 0.321 g of NiCl2·6H2O and 0.321 g of CoCl2·6H2O were added. After continuous stirring at room temperature for 8 hours, the mixture was transferred to a polytetrafluoroethylene liner of a hydrothermal autoclave, and the Cu(OH)2 / CF obtained in step (1) was placed therein. After sealing, the mixture was placed in an oven at 150°C for 10 hours. Subsequently, the mixture was taken out, washed with dimethylformamide, ethanol, and water in sequence, and dried to obtain a dark brown CoNiCu-MOF@Cu2O / CF.
[0039] (3) 0.203 g Ni(NO3)2·6H2O and 0.203 g Co(NO3)2·6H2O were dissolved in 30 mL ethanol solution and stirred evenly. The above solution was then transferred to a 50 mL stainless steel reactor and the prepared CoNiCu-MOF@Cu2O / CF was placed in it. After sealing, the reactor was placed in an oven and kept warm at 110°C for 4 hours. Subsequently, it was taken out for washing and drying to obtain a bifunctional water electrolysis catalyst CoNiCu-LDH@CuO / CF composite material.
[0040] Embodiment 3:
[0041] A copper-based self-supporting water electrolysis catalyst, the preparation process of which comprises the following steps:
[0042] (1) First, a piece of copper foam (CF) is ultrasonically cleaned in acetone, ethanol and deionized water in turn to remove surface impurities. The cleaned CF is immersed in an aqueous solution containing NaOH (2.0 M) and (NH4)2S2O8 (0.1 M) for about 10 to 30 min. The light blue Cu(OH)2 / CF is taken out from the solution, washed, dried and set aside.
[0043] (2) First, 0.124 g of terephthalic acid was weighed and placed in a beaker, and then ethanol, ultrapure water, and organic solvent dimethylformamide (wherein the volume ratio of dimethylformamide, alcohol, and ultrapure water was 12:1:1) were added in sequence. After stirring at room temperature, 0.296 g of NiSO4·6H2O and 0.28 g of (CH3COO)2Co·4H2O were added. After continuous stirring at room temperature for 6 hours, the mixture was transferred to a polytetrafluoroethylene liner of a hydrothermal autoclave, and the Cu(OH)2 / CF obtained in step (1) was placed therein. After sealing, the mixture was placed in an oven at 120°C for 14 hours. Subsequently, the mixture was taken out, washed with dimethylformamide, ethanol, and water in sequence, and dried to obtain a dark brown CoNiCu-MOF@Cu2O / CF.
[0044] (3) 0.5 g Ni(NO3)2·6H2O and 0.5 g Co(NO3)2·6H2O were dissolved in 30 mL ethanol solution and stirred evenly. The above solution was then transferred to a 50 mL stainless steel reactor and the prepared CoNiCu-MOF@Cu2O / CF was placed in it. After sealing, the reactor was placed in an oven and kept at 140°C for 2 hours. Subsequently, it was taken out for washing and drying to obtain a bifunctional water electrolysis catalyst CoNiCu-LDH@CuO / CF composite material.
[0045] Comparative Example 1:
[0046] The difference between Comparative Example 1 and Example 1 is that only step (1) is performed to obtain the Cu(OH)2 / CF composite material.
[0047] Comparative Example 2:
[0048] The difference between Comparative Example 2 and Example 1 is that step (3) is omitted, and the rest is the same as Example 1 to obtain a CoNiCu-MOF@Cu2O / CF composite material (see Figure 6 ).
[0049] The products obtained in Example 1 and Comparative Examples 1 to 2 were used as catalysts to perform water electrolysis and hydrogen evolution tests in a solution containing 1.0 M KOH as the electrolyte. The electrochemical measurements were performed on an electrochemical workstation (CHI750E) using a standard three-electrode system, in which the Hg / HgO electrode was the reference electrode and the graphite electrode was the counter electrode. The products prepared in Example 1 and Comparative Examples 1 to 2 of the present invention were used as working electrodes (geometric area 1 cm×1 cm). Linear sweep voltammetry (LSV) was performed in an O2 saturated electrolyte at 5 mV s -1 The scan rate is measured, formula E vs.RHE =E vs.Hg / HgO +0.059×Ph+0.098 calculated potential and the potential of the reversible hydrogen electrode (RHE). At a current density of 200 mA cm -2The electrochemical stability was tested by chronoamperometric curve under the condition of .
[0050] The results are as follows Figure 1 As shown, Figure 1 -a is the OER performance of Example 1, Comparative Example 1, and Comparative Example 2, Figure 1 -c is the HER performance of Example 1, Comparative Example 1, and Comparative Example 2. It can be seen that CoNiCu-LDH@CuO / CF has the lowest overpotential at a current density of 100 mA cm -2 The oxygen evolution overpotential of the material is 286mV, and the hydrogen evolution overpotential is 262mV. The EIS (1-b, 1-c) results show that in the OER and HER tests, the CoNiCu-LDH@CuO / CF composite material has the smallest internal resistance compared with the CoNiCu-MOF@Cu2O / CF composite material and the Cu(OH)2 / CF composite material, which is beneficial to reduce the polarization phenomenon of the catalyst during the catalytic process and can effectively reduce the overpotential of the catalyst during the catalytic process.
[0051] Figure 2 Polarization curve of CoNiCu-LDH@CuO / CF self-supporting electrode as a bifunctional catalytic material in alkaline electrolyte. -2 The full water decomposition cycle lasts for 24 hours with almost no attenuation.
[0052] Figure 3 This is the SEM image of CoNiCu-LDH@CuO / CF material, which shows that CoNiCu-LDH nanosheets self-assemble into nanoflower cluster structures.
[0053] Figure 4 TEM image of CoNiCu-LDH@CuO / CF material, highlighting the nanosheet structure of CoNiCu-LDH.
[0054] Figure 6 This is the SEM image of the CoNiCu-MOF@Cu2O / CF material, which shows that after the MOF engineering is completed, the CoNiCu-MOF nanosheets are self-assembled and randomly arranged on the Cu(OH)2 / CF substrate.
[0055] The OER performance of the catalyst prepared in the example was then further compared with that of the catalyst recorded in the literature using an electrochemical workstation LSV test, and the test solution was 1M KOH, as shown in Table 1.
[0056] Table 1
[0057]
[0058] References:
[0059] [1]L.Hu,T.Xiong,R.Liu,Y.Hu,Y.Mao,M.J.T.Balogun,Y.Tong,Co3O4@Cu-BasedConductive Metal-Organic Framework Core-Shell Nanowire ElectrocatalystsEnable Efficient Low-Overall-Potential Water Splitting,Chem-Eur.J.25(26)(2019)6575-6583,https: / / doi.org / 10.1002 / chem.201900045.
[0060] [2]J.S.Shaikh,R.C.Pawar,R.S.Devan,Y.R.Ma,P.P.Salvi,S.S.Kolekar,P.S.Patil,Synthesis and characterization of Ru doped CuO thin films forsupercapacitor based on Bronsted acidic ionic liquid,Electrochimi.Acta 56(5)(2011)2127-2134,https: / / doi.org / 10.1016 / j.electacta.2010.11.046.
[0061] [3]Z.Sun,L.Lin,C.Nan,H.Li,G.Sun,X.Yang,Amorphous Boron Oxide CoatedNiCo Layered Double Hydroxide Nanoarrays for Highly Efficient OxygenEvolution Reaction,Acs.Sustain.Chen.Eng.6(11)(2018)14257-14263,https: / / doi.org / 10.1021 / acssuschemeng.8b02893.
[0062] [4]L.Tabassum,H.Tasnim,S.Shubhashish,I.Perera,T.Bhosale,M.Li,S.March,M.K.Islam,S.L.Suib,Selenium-doped copper oxide nanoarrays:Robustelectrocatalyst for the oxygen evolution reaction with ultralowoverpotential,Appl.Mater.Today 27(2022)101485,https: / / doi.org / 10.1016 / j.apmt.2022.101485.
[0063] [5]H.Liang,F.Meng,M.Caban-Acevedo,L.Li,A.Forticaux,L.Xiu,Z.Wang,S.Jin,Hydrothermal continuous flow synthesis and exfoliation of NiCo layereddouble hydroxide nanosheets for enhanced oxygen evolution catalysis,NanoLett.15(2)(2015)1421-1427,https: / / doi.org / 10.1021 / nl504872s.
[0064] [6]C.Yu,Z.Liu,X.Han,H.Huang,C.Zhao,J.Yang,J.Qiu,NiCo-layered doublehydroxides vertically assembled on carbon fiber papers as binder-free high-active electrocatalysts for water oxidation,Carbon 110(2016)1-7,https: / / doi.org / 10.1016 / j.carbon.2016.08.020.
[0065] [7]F.Gu,Q.Zhang,XH Chen,T.Li,HC Fu,HQ Luo,NB Li,Electronic regulation and core-shell hybrids engineering of palm-leaf-like NiFe / Co(PO3)2 bifunctional electrocatalyst for efficient overall water splitting,Int.J.Hydrogen Energy 47(66)(2022)28475-28485,https: / / doi.org / 10.1016 / j.ijhydene.2022.06.148. It can be seen from Table 1 above that the CoNiCu-LDH@CuO / CF electrode has excellent electrocatalytic performance.
[0066] In summary, the present invention provides a self-supporting bifunctional water electrolysis catalyst, which is applied to OER and HER and full water splitting performance tests under alkaline conditions, showing a small internal resistance, and can effectively reduce the polarization phenomenon in the electrocatalytic process, so that the catalyst exhibits a lower overpotential in the catalytic process. The present invention loads CoNiCu-LDH on copper foam by a hydrothermal method to form a stable three-dimensional self-supporting structure, simplifies the preparation process, and improves the long-term stability of the catalyst.
[0067] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention are within the scope of protection required by the present invention.
Claims
1. A highly active self-supporting bifunctional water electrolysis catalyst, characterized in that: The catalyst is a nano-flower layer structure of CoNiCu-LDH loaded on the foam copper CF to form a three-dimensional self-supporting stable structure; the catalyst loading is 5-20 mg cm -2 ; The specific preparation method includes: 1) At room temperature, the copper foam is placed in an aqueous solution of NaOH and (NH4)2S2O8 for chemical oxidation to obtain a precursor 1; 2) adding nickel salt, cobalt salt and terephthalic acid to a mixed solution of methylformamide, ethanol and ultrapure water, stirring at room temperature to obtain a mixed solution; placing precursor 1 in the mixed solution to hydrothermally synthesize precursor 2, and washing and drying after the reaction; 3) The precursor 2 obtained in step 2) is immersed in an ethanol solution containing nickel salt and cobalt salt for hydrothermal synthesis, and washed and dried after the reaction to obtain a bifunctional water electrolysis catalyst.
2. A method for preparing the highly active self-supporting bifunctional water electrolysis catalyst according to claim 1, characterized in that: Cu(OH)2 nanowires were directly grown in situ on the surface of copper foam by a redox method and then placed in a Co-containing 2+ and Ni 2+ A core-shell structure precursor is formed in a mixed solution of a metal salt and terephthalic acid, and then the core-shell structure precursor is immersed in a solvent containing a nickel salt and a cobalt salt to form a cobalt-nickel layered double hydroxide (CoNiCu-LDH) on the foamed copper by a solvothermal method; The specific preparation method includes: 1) At room temperature, the copper foam is placed in an aqueous solution of NaOH and (NH4)2S2O8 for chemical oxidation to obtain a precursor 1; 2) adding nickel salt, cobalt salt and terephthalic acid to a mixed solution of methylformamide, ethanol and ultrapure water, stirring at room temperature to obtain a mixed solution; placing precursor 1 in the mixed solution to hydrothermally synthesize precursor 2, and washing and drying after the reaction; 3) The precursor 2 obtained in step 2) is immersed in an ethanol solution containing nickel salt and cobalt salt for hydrothermal synthesis, and washed and dried after the reaction to obtain a bifunctional water electrolysis catalyst.
3. The method for preparing the highly active self-supporting bifunctional water electrolysis catalyst according to claim 2, characterized in that: In the step 1), the final concentration of NaOH in the aqueous solution of NaOH and (NH4)2S2O8 is 1 mol / L-5 mol / L, and the concentration ratio of NaOH to (NH4)2S2O8 is 5:1-20:
1.
4. The method for preparing the highly active self-supporting bifunctional water electrolysis catalyst according to claim 2, characterized in that: The nickel salt, cobalt salt and terephthalic acid are added to a mixed solution, and the total final concentration of the nickel salt, cobalt salt and terephthalic acid in the mixed solution is 1mmol / L-3mmol / L, wherein the molar ratio of the nickel salt, cobalt salt and terephthalic acid is 1:1:1.5-1:1:
3.
5. The method for preparing the highly active self-supporting bifunctional water electrolysis catalyst according to claim 4, characterized in that: The mixed solution is prepared by sequentially mixing methylformamide, ethanol and ultrapure water in a volume ratio of 12:1:
1.
6. The method for preparing the highly active self-supporting bifunctional water electrolysis catalyst according to claim 2, characterized in that: The nickel salt is one or more of nickel nitrate hexahydrate, nickel sulfate hexahydrate, nickel chloride hexahydrate, and nickel bromide; the cobalt salt is one or more of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, and cobalt acetate tetrahydrate.
7. The method for preparing the highly active self-supporting bifunctional water electrolysis catalyst according to claim 2, characterized in that: In the step 2), the precursor 1 is placed in a mixed solution at 70°C-150°C for a solvent thermal synthesis reaction for 10-14 hours, washed with ethanol after the reaction, and dried at 60°C-100°C to obtain the precursor 2.
8. The method for preparing the highly active self-supporting bifunctional water electrolysis catalyst according to claim 2, characterized in that: In the step 3), the precursor 2 obtained in the step 2) is immersed in an ethanol solution containing nickel salt and cobalt salt at 110°C-140°C for hydrothermal synthesis for 2-4h, and after the reaction, it is washed with ethanol and dried at 60°C-100°C to obtain a bifunctional water electrolysis catalyst; wherein the total final concentration of nickel salt and cobalt salt in ethanol is 1mmol-3mmol, and the molar ratio of nickel salt to cobalt salt is 1:
1.
9. An application of the water electrolysis catalyst according to claim 1, characterized in that: Application of the catalyst in water electrolysis reaction.
Citation Information
Patent Citations
Electro-catalytic acetylene hydrogenation reaction system and electro-catalytic acetylene hydrogenation reaction method using same
CN112853383A
Difunctional self-supporting electrolyzed water catalytic material as well as preparation method and application thereof
CN114921796A